FATIGUE DESIGN FOR POWERTRAIN RUBBER MOUNT - HU HaoJu; DENG XiaoQiang; YE ShuBin; GUO ShaoLiang (Jixie qiangdu)
Based on material tensile test data of the vehicle powertrain anti-torsion rubber mount, parameters of the Ogden hyper-elastic constitutive model were obtained by using Abaqus. Then the ε-N fatigue curve of its rubber material was tested according to the strain fatigue theory of rubber. The finite element model was calibrated based on the stiffness test of the rubber mount. The fatigue life of the rubber mount was calculated and optimized according to the fatigue bench test. Finally, the fatigue life of the rubber structure in the whole vehicle driving endurance test was predicted.